Incidence of bloodstream infections in small bowel transplant recipients receiving selective decontamination of the digestive tract: A single‐center experience. (2nd September 2015) - Galloway, David; Danziger‐Isakov, Lara; Goldschmidt, Monique; Hemmelgarn, Trina; Courter, Joshua; Nathan, Jaimie D.; Alonso, Maria; Tiao, Greg; Fei, Lin; Kocoshis, Samuel
Abstract Pediatric patients undergoing small bowel transplantation are susceptible to postoperative CLABSI. SDD directed against enteric microbes is a strategy for reducing CLABSI. We hypothesized that SDD reduces the frequency of CLABSI, infections outside the bloodstream, and allograft rejection during the first 30 days following transplant. A retrospective chart review of 38 pediatric small bowel transplant recipients at CCHMC from 2003 to 2011 was conducted. SDD antimicrobials were oral colistin, tobramycin, and amphotericin B. The incidence of CLABSI, infections outside the bloodstream, and rejection episodes were compared between study periods. The incidence of CLABSI did not differ between study periods (6.9 CLABSI vs. 4.6 CLABSI per 1000 catheter days; p = 0.727), but gram positives and Candida predominated in the first 30 days. Incidence of bacterial infections outside the bloodstream did not differ (p = 0.227). Rejection occurred more frequently during the first month following transplant (p = 0.302). SDD does not alter the incidence of CLABSI, bacterial infections outside the bloodstream, or allograft rejection in the immediate 30 days post‐transplantation. However, SDD does influence CLABSI organism types (favoring gram positives and Candida) and Candidal infections outside the bloodstream.